Expectations of the working enviroment – encounter civilization on the ocean liner - Balogh, Andrea; Juhászné Klér, Andrea; Rudnák, Ildikó (Studia Mundi – Economica, 2016)
The world of ocean liners is full of secrets for many people, but, of course, it is a very special working environment by all means. During our examination we have undertaken to map the expectations and motivations of the employees coming from several continents together with some similarities and differences. Based on our results the similarities lying in the background of motivation can enhance cooperation and more intense encounters to a great extent even in spite of the intensive mental and physical burdens.
Keywords: cohabitation; working environment; connecting cultures; mental load; motivation